Role of Intravenous Iron Sucrose in Correction of Anemia in Antenatal Women with Advanced Pregnancy - Gupta, Avantika (Indian J Hematol Blood Transfus, 2014)
The aim of this study is to observe rise in haematological parameters after treatment with iron sucrose in antenatal patients with moderate anemia with period of gestation 32 to 35 weeks. The study included 45 antenatal patients with period of gestation from 32 to 35 weeks having iron deficiency anemia with haemoglobin levels 7–9 g% and serum ferritin levels less than 12 ng/mL. Intravenous iron sucrose was given in the dose of 200 mg on alternate days, according to the calculated dose. The mean haemoglobin and red blood cell indices were compared on days 7, 14, 21, 28 and at the time of delivery from the baseline value. There was a statistically significant rise in haemoglobin value from baseline on days 14, 21, 28 as well as at the time of delivery (p value <0.0001). The mean rise in haemoglobin values was 0.56 g% on day 14, 1.44 g% on day 21 and 2.0 g% on day 28. At the time of delivery, mean haemoglobin was 11.24 g%. After 28 days of treatment, there was a statistically significant rise in the levels of serum ferritin from 10.33 ± 3.8 ng/mL to 36.89 ± 5.7 ng/mL. Thus, earlier response achieved by iron sucrose can be utilised in the patients presenting at an advanced period of gestation with iron deficiency anemia.